2007
DOI: 10.1080/10401330701364551
|View full text |Cite
|
Sign up to set email alerts
|

Formal Peer-Teaching in Medical School Improves Academic Performance: The MUSC Supplemental Instructor Program

Abstract: The activity of formal peer-teaching was beneficial to the SI leaders' own academic success as measured by GPA and USMLE test scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 9 publications
2
70
0
1
Order By: Relevance
“…First, Wong et al (2007) found that peer educator academic performance was enhanced. [22] Second, Gözüm et al (2010) recommended that peers can support learning through continuous contact. Peer education can be utilized to enhance early diagnosis of breast tumors and breast cancer attentiveness in asymptomatic females.…”
Section: Discussionmentioning
confidence: 99%
“…First, Wong et al (2007) found that peer educator academic performance was enhanced. [22] Second, Gözüm et al (2010) recommended that peers can support learning through continuous contact. Peer education can be utilized to enhance early diagnosis of breast tumors and breast cancer attentiveness in asymptomatic females.…”
Section: Discussionmentioning
confidence: 99%
“…This prepares the nursing students for their future roles as educators, builds their self esteem, and enhances their psychomotor skills and their attitudes [16][17][18][19][20][21] . As for nurse educators and faculty, peer teaching may reduce their workload in teaching, and provides them with more opportunities to observe and provide feedback to their students regarding their performance [22][23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…The perceptions of student learners are useful in evaluating the program but it is also important that being in attendance at the sessions is effective in the transfer of knowledge (Wong et al, 2007). In a comprehensive retrospective study Ten Cate et al (2012) concluded that near peer tutoring has similar benefits to faculty teaching in terms of academic achievement.…”
Section: Consideration 9: Ensure Quality Control and Reputationmentioning
confidence: 99%
“…In a comprehensive retrospective study Ten Cate et al (2012) concluded that near peer tutoring has similar benefits to faculty teaching in terms of academic achievement. This study, like a few others in the field, compared end of module examination scores, although a common alternative approach is to measure knowledge gain via pre and post testing (Topping, 1996;Wong et al, 2007;Ten Cate et al, 2012;Rees et al, 2016). Surprisingly, only a small number of published studies on NPT in anatomy have investigated the impact of NPT on student learning outcomes.…”
Section: Consideration 9: Ensure Quality Control and Reputationmentioning
confidence: 99%